1984
DOI: 10.1111/j.1475-4932.1984.tb00871.x
|View full text |Cite
|
Sign up to set email alerts
|

The Micro Effects of Inflation on Corporate Taxation and Profitability: Some Empirical Evidence for Seventeen Industry Groups*

Abstract: This study provides some estimates for the following micro effects of inflation: the depreciation effect; the inventory effect; and the net monetary effect. The results indicate that these distributive effects of inflation lead to non‐trivial reallocations of wealth between the different sectors of the economy. Furthermore, the study identifies those industry groups which have benefited from these effects and those industry groups which have ‘lost out’ due to these effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…For example, Anderson et al (1983), Matolcsy (1984), and Ferris and Makhija (1988) find evidence supporting the tax hypothesis; Gonedes (1981), Geske and Roll (1983), Kaul (1987), and Lee (2010) do not find support; and Bernard and Hayn (1986) find mixed evidence. Also, French et al (1983), Bernard (1986), and Pearce and Roley (1988) indirectly examine the tax hypothesis using stock returns around inflation announcements.…”
Section: Introductionmentioning
confidence: 90%
“…For example, Anderson et al (1983), Matolcsy (1984), and Ferris and Makhija (1988) find evidence supporting the tax hypothesis; Gonedes (1981), Geske and Roll (1983), Kaul (1987), and Lee (2010) do not find support; and Bernard and Hayn (1986) find mixed evidence. Also, French et al (1983), Bernard (1986), and Pearce and Roley (1988) indirectly examine the tax hypothesis using stock returns around inflation announcements.…”
Section: Introductionmentioning
confidence: 90%
“…Matolcsy's (1984) study covered the period 1969-1979 and it indicated that the impact of not specifically adjusting for inflation had a significant and adverse effect on after-tax business income. Matolcsy's (1984) study covered the period 1969-1979 and it indicated that the impact of not specifically adjusting for inflation had a significant and adverse effect on after-tax business income.…”
Section: Depreciation Allowancesmentioning
confidence: 99%
“…The failure of the current definition of taxable income to make allowances for the appreciating value of depreciable assets has been addressed by governments through accelerated depreciation rates, in an attempt at an offset for the non-neutrality. Matolcsy's (1984) study covered the period 1969-1979 and it indicated that the impact of not specifically adjusting for inflation had a significant and adverse effect on after-tax business income.…”
Section: Depreciation Allowancesmentioning
confidence: 99%